2023
DOI: 10.1002/ptr.7730
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of randomized controlled trials investigating the effect of the curcumin and piperine combination on lipid profile in patients with metabolic syndrome and related disorders

Abstract: Metabolic syndrome is characterized by multiple metabolic disorders. Several studies indicated that curcumin plus piperine could affect lipids profiles in various diseases.The present meta-analysis aims to assess the effect of curcumin plus piperine on lipid profiles in patients with MetS and associated disorders using a systematic review and meta-analysis of randomized controlled trials. Trials were searched by several electronic databases up to May 2022. The Comprehensive Meta-Analysis (CMA) version3 softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…These findings are generally in accordance with the results from previous meta‐analyses, which also identified a significant correlation between curcumin plus piperine supplementation and improvements in TC concentration in patients suffering from MetS (Hosseini et al, 2023). However, our results are not consistent with the previous meta‐analysis that reported a reduction in LDL‐C levels after supplementation with C. annuum (Jang et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are generally in accordance with the results from previous meta‐analyses, which also identified a significant correlation between curcumin plus piperine supplementation and improvements in TC concentration in patients suffering from MetS (Hosseini et al, 2023). However, our results are not consistent with the previous meta‐analysis that reported a reduction in LDL‐C levels after supplementation with C. annuum (Jang et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Hoseini et al review (2023) [ 34 ] showed that the co-administration of curcumin and piperine, independently of the dose, in patients suffering from metabolic syndrome, can restore optimal blood lipid values, with a large reduction of total cholesterol and LDL, but no effect on TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…From the previous section, there are many reasons why curcumin-based FDC products are attractive for cholesterol management. Curcumin has been shown to inhibit key enzymes involved in the synthesis of cholesterol, such as HMG-CoA reductase. By reducing the activity of this enzyme, the production of cholesterol in the liver can be diminished.…”
Section: Challenges Of Using Curcumin-based Fdc Productsmentioning
confidence: 99%